Old Habits Die Hard! Technology Savvy Students and Internet-Based Learning Technology Uptake - Pinto. D, Praveen (2012)
The presence of Information Technology (IT) is seen in every part of human life. IT is used in every corner of social activities, including education as it has the capability of lifting the quality and standard of knowledge acquisition, sharing and utilization. The advancement of IT saw the birth of Internet technology. Research on the use of Internet technology for learning purpose is growing. A similar focus in the context of Malaysia however remains scarce. This research fills the knowledge gap by examining the role of technology savvy habits of students in using Internet-based learning technology. A total of 200 students of INTI International University were surveyed in June 2012. The collected data was using the Structural Equation Modeling (SME) technique. The empirical results suggest that technology use habit is a significant moderator between continuance intentions to use Internet based learning technology and continuance usage of Internet-based learning technology. The results also showed that the absence of technology use habit as a moderator reduces the relationship strength between continuance intentions and continuance usage. The findings lead to the conclusion that the technology savvy students would have the intention to continuously use Internet based learning technology which then leads to actual usage of the technology for learning purpose. Thus INTI International University in specific and other education institutions in Malaysia, in general, would need to make initiatives to understand the expectations and usage experience level of students and provide on par Internet based learning technology.